Cucurbituril—assisted sensitive fluorescence detection and quantitation of naproxen drug in wastewater samples: Guest-host characterization and HPLC investigation - Meetani, Mohammed A.; Alhalabi, Ahmad; Al-Tabaji, Mohammed K.; Al-Hemyari, Abdulla; Saadeh, Haythem A.; Saleh, Na’il (Frontiers in Chemistry, 2022)
Sensitive spectrofluorometric and liquid chromatography with fluorescence detection methods have been developed for detection and determination of naproxen drug in the presence of cucurbit7uril (CB7). Fluorescence signals have been improved with the addition of CB7 to the drug aqueous solution. Fluorescence spectroscopy, mass spectrometry, 1H-NMR, and liquid chromatography with fluorescence detection were used to investigate the guest-host interaction of naproxen drug and cucurbiturils. Naproxen was found to form a supramolecular complex with CB7 that had a high formation constant. The optimal conditions for the interaction were discovered using spectroflurometry to be 0.2 mg/ml of CB7, 2.4 μg/ml of naproxen drug, and pH10. A 1:1 complex between naproxen and CB7 is revealed by proton NMR and tandem mass spectrometry. Using the standard addition calibration method, an HPLC with a fluorescence detector was used to detect naproxen in influent and effluent wastewater samples. Finally, it was discovered that the measured concentrations of naproxen in the influent and the effluent wastewater were 1.87 × 10−4 ppb and 2.1 × 10−5 ppb, respectively. This was done by sample enrichment, which reduced the 1000 mL into 1 ml.